Pseudovertical Temperature Profiles Give Insight into Winter Evolution of the Atmospheric Boundary Layer over the McMurdo Dry Valleys of Antarctica - Zawar-Reza, Peyman; Katurji, Marwan; Soltanzadeh, Iman; Dallafior, Tanja; Zhong, Shiyuan; Steinhoff, Daniel; Storey, Bryan; Cary, S. Craig (Journal of Applied Meteorology and Climatology, 2013)
ISSN:1558-8424 ISSN:0733-3021 ISSN:0021-8952 ISSN:0894-8763 ISSN:1558-8432